Elaboração e avaliação de um programa de ensino sobre educação sexual para professores do ensino fundamental I - Moura, Carla Elias de (2018)
The objective of this study was to evaluate the effectiveness of a Sex Education Education Program applied to fourth and fifth year primary school teachers from Foz do Iguaçu - PR and to identify which components of this program were considered by teachers as effective in the production of changes indicative of improvement in the level of comfort and capacity to work with sex education in the age group of 9 to 11 years. A total of 83 teachers (03 males and 80 females) participated in the present study, most of them aged between 30 and 45 years, teaching in the fourth and fifth year of the public school, distributed in twenty groups. The elaborate Teaching Program was titled "What I answer? - Sexual Education Program for Teachers”, with 3 hours of duration, and its format was designed to standardize procedures and use the use of role playing technique. Participants responded to an instrument with problem situations on sexuality issues before and after training. In the end, they also answered an instrument for evaluating the components of the Teaching Program. The data were analyzed by means of parametric statistics between dependent samples (Test T), descriptive statistics and content analysis of Bardin (1970). The results showed that there was a statistically significant change in the level of comfort and capacity of teachers after the Teaching Program. The content analysis showed that the initial difficulties of teachers were embarrassing with questions about the sexual act, which declined after the Teaching Program, while the sexual behavior category was highlighted as the most difficult after the training. Regarding the evaluation of the Program, the best evaluated component was the Hot Seat technique. Thus, it was concluded that the proposed Program proved to be effective in helping teachers improve the level of ability and comfort to work on some themes of sexuality. The evaluation of the components of the program provided important data for possible reformulations of the program in order to assist professionals in working with this theme. This study showed that the structuring of teaching programs for teacher training produces behaviors relevant to the development of sex education in the school environment.